2017
DOI: 10.1111/ajt.14100
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Hepatitis C Virus Resistance After Pig Liver Transplantation—A Proof of Concept of Liver Graft Modification Using Warm Ex Vivo Perfusion

Abstract: Normothermic ex vivo liver perfusion (NEVLP) offers the potential to optimize graft function prior to liver transplantation (LT). Hepatitis C virus (HCV) is dependent on the presence of miRNA(microRNA)-122. Miravirsen, a locked-nucleic acid oligonucleotide, sequesters miR-122 and inhibits HCV replication. The aim of this study was to assess the efficacy of delivering miravirsen during NEVLP to inhibit miR-122 function in a pig LT model. Pig livers were treated with miravirsen during NEVLP or cold storage (CS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 28 publications
0
58
0
Order By: Relevance
“…Normothermic conditions offer the chance for pharmacologic interventions that are dependent on an active metabolism of the graft . For example, Goldaracena et al demonstrated the feasibility of anti‐inflammatory treatment and inhibition of hepatitis C virus replication during NEVLP of porcine liver grafts . However, large animal models of NEVLP are cost intensive and comprise logistic implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normothermic conditions offer the chance for pharmacologic interventions that are dependent on an active metabolism of the graft . For example, Goldaracena et al demonstrated the feasibility of anti‐inflammatory treatment and inhibition of hepatitis C virus replication during NEVLP of porcine liver grafts . However, large animal models of NEVLP are cost intensive and comprise logistic implications.…”
Section: Discussionmentioning
confidence: 99%
“…(11) For example, Goldaracena et al demonstrated the feasibility of anti-inflammatory treatment and inhibition of hepatitis C virus replication during NEVLP of porcine liver grafts. (23,25) However, large animal models of NEVLP are cost intensive and comprise logistic implications. Standardized small animal models for basic research on machine perfusion of the liver and large sets of dose-response and timing studies on pharmacological conditioning are not available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, bioengineering organs through decellularization and repopulation with specific cell types have been explored in ex vivo MP and bioreactor platforms by our group and others, 58,111,[116][117][118] though the current timeline of ex vivo MP does not allow us to effectively assess cell engraftment and function. Extended preservation time could enable development of improved cell-based therapies and allow for cell uptake and engraftment prior to transplantation.…”
Section: Current Limitations and Future Outlookmentioning
confidence: 99%
“…The main potential of MP is not only simple resuscitation of donor organs but also the possibility to administer organ-specific therapies with the avoidance of systemic side effects, which is in contrast to all previously described direct donor and recipient preconditioning methods. In LT, efforts were reported in experimental settings to inactivate miRNA-122 utilizing normothermic MP (NMP) in order to prevent hepatitis C virus (HCV) infection after transplantation of HCV-positive organs [37], whereas these are of minor importance since the advent of the new, highly effective anti-HCV treatment options.…”
Section: Approaches For Preconditioning Organs In Order To Improve Trmentioning
confidence: 99%